Pelatihan Pasar Modal Memoderasi Pengetahuan Investasi dan Kemajuan Teknologi Terhadap Minta Investasi Mahasiswa - Firdiyansyah, Indra; Rani Susanthi, Putu; Purwaka Sari, Asih; Rina; Afrinanda; Wulandari, Kiki; Yusyawiru, Nurul (Program Studi Manajemen FEBM UMRAH, 2024)
This study aims to analyze the effect of accounting conservatism practices with accrual measures in corporate governance mechanisms on earnings quality, this research method uses quantitative time series data, data from BEI for three years from 2014-2016, the number of research data is 273. Data processing is tested with statistics through classical assumptions and hypothesis testing with the T-Test, F-Test and Determination test. The results of the study prove that accounting conservatism has a significant effect on earnings quality by 23.3%. Accounting conservatism with the accrual measure through corporate governance mechanisms has a significant effect on earnings quality by 27.10% and accounting conservatism on market value measures in a significant effect on earnings quality by 24.3%.